2022
DOI: 10.1136/bmjopen-2022-062437
|View full text |Cite
|
Sign up to set email alerts
|

Health professionals’ experience of implementing and delivering a ‘Community Care’ programme in metropolitan Melbourne: a qualitative reflexive thematic analysis

Abstract: ObjectivesTo explore the experiences of health professionals involved in delivering a multidisciplinary Community Care programme that provides a transitional care coordination service for patients visiting a tertiary hospital service in Melbourne, Australia.DesignReflexive thematic analysis was used to identify themes from descriptions of delivering the programme, including its perceived strengths and challenges.Participants12 healthcare professionals from four disciplines working in the Community Care program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
1
6
1
Order By: Relevance
“…In line with Baxter et al ( 21 ), technology can be used as a way to improve safety during the transition. Therefore the use of relatable information support systems in holistic care is essential to support the seamless transfer of electronic medical records and prior visit records between hospital, community, and home care for care coordination ( 54 ). In addition, consistent with previous research, the navigator role needs to be introduced in “siloed” systems as a link between patients, informal caregivers, and health care providers during transitions in the health care system ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with Baxter et al ( 21 ), technology can be used as a way to improve safety during the transition. Therefore the use of relatable information support systems in holistic care is essential to support the seamless transfer of electronic medical records and prior visit records between hospital, community, and home care for care coordination ( 54 ). In addition, consistent with previous research, the navigator role needs to be introduced in “siloed” systems as a link between patients, informal caregivers, and health care providers during transitions in the health care system ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…9,28 The ability to effectively recruit/train multidisciplinary staff with sufficient generalist skills to service the clinical heterogeneity of HITH patients, whilst also enabling the effective management of complex cases is a significant challenge. 29,30 This is worthy of future investigation, especially for services that combine several sub-speciality areas such as acute, rehabilitation and geriatric evaluation and management services.…”
Section: Discussionmentioning
confidence: 99%
“…1,39 Leveraging change agents, such as programme champions, and utilising social media platforms were found to help promote the value of community paramedicine models of care, dispel misconceptions, and build trust among other healthcare professionals 40 and the community. Prior studies in palliative care 41 and hospital-based readmission risk programmes 42,43 have revealed that common misconceptions regarding the programmes’ roles can be hindered by persistent miscommunication. Overcoming these issues may be achieved through clear purpose statements and the use of change agents to dispel misconceptions.…”
Section: Discussionmentioning
confidence: 99%